Sustainable performance in tourism SMEs: a soft modeling approach - Núñez-Ríos, Juan E.; Sánchez-García, Jacqueline Y.; Ramirez-Nafarrate, Adrian (My University, 2022)
Purpose This paper aims to present a model to incentivize sustainable performance (SUP) in small- and medium-sized tourism by strengthening inner relations to adapt to a complex environment. Design/methodology/approach The authors adopted the systemic approach complementing analytic, tourism, partial least squares path modeling (PLS-PM), social network analysis (SNA) and systemic approach tools as follows: frame the problem through the soft systems methodology and SNA and identify the conflicting relationships; apply PLS-PM to validate the model; and propose new interactions for small- and medium-sized enterprises conducive to SUP based on the viable system model. Findings Considering the results, the authors pinpointed factors and relationships managers can address to foster SUP, highlighting the need to reinforce feedback loops and reduce inconsistencies between primary operations with coordination and management mechanisms. Research limitations/implications This work is limited to the organizational domain. Although the results apply to the Mexican context, this could be overcome using methodological complementarity to extend the ideas to other organizations. Practical implications This study invites discussing methods and viewpoints for rethinking SUP because of multiple factors. This requires adopting methodological complementarity to generate alternatives and reconfiguring inner organizational interactions. Originality/value The model captures minimum but sufficient components advising leaders about SUP. This proposal differs from previous studies because it suggests exploiting methodological complementarity to capture the insights of key operative actors to conceive the model. Hence, the authors suggest new relations among organizational factors so managers can develop strategies for adaptability.